1981
DOI: 10.1084/jem.154.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Antigen recognition. V. Requirement for histocompatibility between antigen-presenting cell and B cell in the response to a thymus-dependent antigen, and lack of allogeneic restriction between T and B cells.

Abstract: The restrictions imposed by the major histocompatibility complex on T-B-antigen-presenting cell (APC) interactions were studied with an in vivo adoptive transfer system, using mutually tolerant T and B cells taken from one-way fetal liver chimeras. It was found that the B cells and adoptive recipient (which provides APC function) have to share determinants encoded by the left-hand end of the H-2 complex for cooperation, whereas there is apparently no such requirement for T-B cell syngeneicity. Suppression aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…In this primary T cell-independent response, the authors proposed that the responding B cells might recognize self-MHC products on the macrophage. Similar conclusions have been drawn by Nisbet-Brown et al (15) in their recently published work on the antibody responses to the T-dependent antigens trinitrophenylkeyhole limpet hemocyanin. It is interesting to note that the latter study suggests that B cells do not adaptively differentiate in parent ~ F1 chimeras.…”
Section: H-2 Axq H-2 ~ ~ H-2 Axq H-2 ~Q ~ H-2 ~ and H-2 ~Q ~ H-2 Qsupporting
confidence: 86%
“…In this primary T cell-independent response, the authors proposed that the responding B cells might recognize self-MHC products on the macrophage. Similar conclusions have been drawn by Nisbet-Brown et al (15) in their recently published work on the antibody responses to the T-dependent antigens trinitrophenylkeyhole limpet hemocyanin. It is interesting to note that the latter study suggests that B cells do not adaptively differentiate in parent ~ F1 chimeras.…”
Section: H-2 Axq H-2 ~ ~ H-2 Axq H-2 ~Q ~ H-2 ~ and H-2 ~Q ~ H-2 Qsupporting
confidence: 86%
“…Although such complex recognition is characteristic of T cell specificity, there have been reports that imunoglobulins can also be restricted to the recognition of certain antigenic determinants in the context of cell surface antigens (10,11). Similarly, although many studies have indicated that B cell stimulation need not be haplotype restricted (4,(27)(28)(29), a few recent investigations have implied that under certain conditions B cells may only be stimulated by antigen presented in the context of cells of an appropriate H-2 haplotype (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, antigen-specific cytolytic T lymphocytes are restricted in effector function by the major histocompatibility complex (MHC) 1 of the stimulatory antigen-bearing cells (6)(7)(8)(9). Such recognition, which apparently dominates the T cell specificity repertoire, has recently been implicated in antigen recognition by B cells as well (10)(11)(12)(13)(14)(15). However, because many antibodies can bind to antigens in the absence of presenting cells, the portion of antibody binding that may be dependent on antigen presentation in the context of a presenting cell may generally be obscured by antibodies in the population capable of binding the antigen per se.…”
mentioning
confidence: 99%
“…It has recently been demonstrated (12)(13)(14)(15)) that B cells, as well as TH cells, can express requirements for recognition of self-MHC determinants expressed by the accessory cells with which they interact. In particular, it has recently been shown (15) that B cells from long-term radiation bone marrow chimeras express a requirement for MHC-restricted self-recognition in TI responses to high concentrations of TNPFicoll.…”
Section: Discussionmentioning
confidence: 99%